Emodin, Physcion, and Crude Extract of Rhamnus sphaerosperma var. pubescens Induce Mixed Cell Death, Increase in Oxidative Stress, DNA Damage, and Inhibition of AKT in Cervical and Oral Squamous Carcinoma Cell Lines - Moreira, Thais Fernanda [UNESP]; Sorbo, Juliana Maria [UNESP]; Souza, Felipe de Oliveira [UNESP]; Fernandes, Barbara Colatto [UNESP]; Marins Ocampos, Fernanda Maria; Soares de Oliveira, Daniella Maria; Arcaro, Carlos Alberto [UNESP]; Assis, Renata Pires [UNESP]; Barison, Andersson; Miguel, Obdulio Gomes; Baviera, Amanda Martins [UNESP]; Soares, Christiane Pienna [UNESP]; et al. (Hindawi Ltd, 2018)
There have been few studies on the pharmacological properties of Rhamnus sphaerosperma var. pubescens, a native Brazilian species popularly known as fruto-de-pombo. The aim of this study was to investigate the scavenging capacity of emodin, physcion, and the ethanolic crude extract of Rhamnus sphaerosperma var. pubescens against reactive oxygen and nitrogen species, as well as their role and plausible mechanisms in prompting cell death and changes in AKT phosphorylation after cervical (SiHa and C33A) and oral (HSC-3) squamous cell carcinoma treatments. Emodin was shown to be the best scavenger of NO center dot and O-2(center dot-), while all samples were equally effective in HOCl/OCl- capture. Emodin, physcion, and the ethanolic extract all exhibited cytotoxic effects on SiHa, C33A, HSC3, and HaCaT (immortalized human keratinocytes, nontumorigenic cell line), involving mixed cell death (apoptosis and necrosis) independent of the caspase activation pathway. Emodin, physcion, and the ethanolic extract increased intracellular oxidative stress and DNA damage. Emodin decreased the activation of AKT in all tumor cells, physcion in HSC3 and HaCaT cells, and the ethanolic extract in C33A and HaCaT cells, respectively. The induction of cancer cell death by emodin, physcion, and the ethanolic crude extract of Rhamnus sphaerosperma var. pubescens was related to an increase in intracellular oxidative stress and DNA damage and a decrease in AKT activation. These molecules are therefore emerging as interesting candidates for further study as novel options to treat cervical and oral carcinomas.